A educação matemática no desenvolvimento profissional de professor(a) no curso de Pedagogia da Universidade Federal de Sergipe - Graça, Janilce Santos Domingues (2011)
The present work has as objective indentify the relations that the students from the Pedagogy course at Universidade Federal de Sergipe establish between didactic and the acquisition of mathematical knowledge lived at different moments of their schooling since basic education until college and analyze the process of mathematical knowledge acquisition as to the concept of number, indentifying and explicitating the appropriations which those teachers effectuated about these elements during the academic formation in Pedagogy. This study was developed from the interpretative paradigm of research through the qualitative nature of research and the ethnographic method. The main instruments of information collection used were questionnaires and autobiographic reports. The present work has as references the investigations from Shulman (1986). Tardif (2002). Garcia (1999). Serrazina (2002). Ponte (1998). Curi (2004). Fiorentini (2002). Kamii (1985). Soares (2009). Silva (2008). Charlot (2005). Lorenzato (2009). Brzezinski (1996). Veiga (1997), among others. In this sense, this research aims to contribute to the institutions and to the society when it comes to the overcoming of challenges in the difficulties of learning mathematical contents and in the formation of teachers in the initial years of basic education.